2015
DOI: 10.1111/mec.13132
|View full text |Cite
|
Sign up to set email alerts
|

Genetic isolation between two recently diverged populations of a symbiotic fungus

Abstract: Fungi are an omnipresent and highly diverse group of organisms, making up a significant part of eukaryotic diversity. Little is currently known about the drivers of fungal population differentiation and subsequent divergence of species, particularly in symbiotic, mycorrhizal fungi. Here, we investigate the population structure and environmental adaptation in Suillus brevipes (Peck) Kuntze, a wind-dispersed soil fungus that is symbiotic with pine trees. We assembled and annotated the reference genome for Su. br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
108
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 61 publications
3
108
4
Order By: Relevance
“…Instead, dispersal limitation seems to have a crucial role in producing the patterns of fungal diversity and community structure that are observed across a range of spatial (see the figure, solid lines (or, where speculative, dashed lines)) and temporal scales (see the figure, y-axis). Evolution of unique bio-geographical assemblages [48][49][50][51] Limited gene flow leads to population differentiation 47,52 Introduction of invasive species disrupts local communities 109 Dispersal limitation may affect species richness and colonization rate for isolated habitats 37 Priority effects increase spatial heterogeneity of assemblages 66,67,68 Dispersal traits influence community assembly 37 Dispersal distance of most spores 37,114,116 Nature Reviews | Microbiology…”
Section: Box 3 | Spore Dispersalmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, dispersal limitation seems to have a crucial role in producing the patterns of fungal diversity and community structure that are observed across a range of spatial (see the figure, solid lines (or, where speculative, dashed lines)) and temporal scales (see the figure, y-axis). Evolution of unique bio-geographical assemblages [48][49][50][51] Limited gene flow leads to population differentiation 47,52 Introduction of invasive species disrupts local communities 109 Dispersal limitation may affect species richness and colonization rate for isolated habitats 37 Priority effects increase spatial heterogeneity of assemblages 66,67,68 Dispersal traits influence community assembly 37 Dispersal distance of most spores 37,114,116 Nature Reviews | Microbiology…”
Section: Box 3 | Spore Dispersalmentioning
confidence: 99%
“…Several recent studies have used molecular 50 and mathematical 125 approaches to quantify the spatial scale of fungal dispersal in natural systems. These studies show that the majority of fungal spores move only centimetres to metres.…”
Section: Box 3 | Spore Dispersalmentioning
confidence: 99%
“…Finally, Branco et al (2015) studied coastal and mountain populations of the Californian fungus, Suillus brevipes, using NGS to reveal unprecedented cryptic speciation and recent divergence of the isolated populations. Just 0.01% of single nucleotide polymorphisms (SNPs) were fixed between the two populations; despite this low divergence, phenotypic variation had begun to characterize the two populations, with a gene potentially involved in enhanced salt tolerance in acidic conditions fixed in the coastal, but not the mountain, populations (Branco et al, 2015).…”
Section: Population Genomic Data Are Relevant To Systems-level Insightsmentioning
confidence: 99%
“…Just 0.01% of single nucleotide polymorphisms (SNPs) were fixed between the two populations; despite this low divergence, phenotypic variation had begun to characterize the two populations, with a gene potentially involved in enhanced salt tolerance in acidic conditions fixed in the coastal, but not the mountain, populations (Branco et al, 2015). This suggests that a selection-based hypothesis might explain the biogeography and macroecology of the two fungal populations, thus demonstrating how comparative population genomic approaches can yield insight into larger scale diversification and ecological processes.…”
Section: Population Genomic Data Are Relevant To Systems-level Insightsmentioning
confidence: 99%
“…When more variable DNA sequences are used for comparison in small organisms, it has been shown that almost nothing is everywhere, whether fungi (5), protists (6), bacteria (7), or archaea (8). Now, population genomics is showing that natural barriers to fungal gene flow occur over geographic distances well below the size of continents (9)(10)(11), with dispersal limitation playing a key role in the assembly of fungal communities (12). When similar variable markers and population genomics can be applied to arbuscular mycorrhizal fungi, we predict that narrowly endemic species and populations will be discovered to be the rule, and what we now call species will be revealed to be collections of distantly related taxa.…”
mentioning
confidence: 99%